Developmental changes in GABA(A) tonic inhibition are compromised by multiple mechanisms in preadolescent dentate gyrus granule cells - Pandit, Sudip (Korean J Physiol Pharmacol, 2017)
The sustained tonic currents (I(tonic)) generated by γ-aminobutyric acid A receptors (GABA(A)Rs) are implicated in diverse age-dependent brain functions. While various mechanisms regulating I(tonic) in the hippocampus are known, their combined role in I(tonic) regulation is not well understood in different age groups. In this study, we demonstrated that a developmental increase in GABA transporter (GAT) expression, combined with gradual decrease in GABA(A)R α(5) subunit, resulted in various I(tonic) in the dentate gyrus granule cells (DGGCs) of preadolescent rats. Both GAT-1 and GAT-3 expression gradually increased at infantile (P(6-8) and P(13-15)) and juvenile (P(20-22) and P(27-29)) stages, with stabilization observed thereafter in adolescents (P(34-36)) and young adults (P(41-43)). I(tonic) facilitation of a selective GAT-1 blocker (NO-711) was significantly less at P(6-8) than after P(13-15). The facilitation of I(tonic) by SNAP-5114, a GAT-3 inhibitor, was negligible in the absence of exogenous GABA at all tested ages. In contrast, I(tonic) in the presence of a nonselective GAT blocker (nipecotic acid, NPA) gradually decreased with age during the preadolescent period, which was mimicked by I(tonic) changes in the presence of exogenous GABA. I(tonic) sensitivity to L-655,708, a GABA(A)R α(5) subunit inverse agonist, gradually decreased during the preadolescent period in the presence of NPA or exogenous GABA. Finally, Western blot analysis showed that the expression of the GABA(A)R α(5) subunit in the dentate gyrus gradually decreased with age. Collectively, our results suggested that the I(tonic) regulation of altered GATs is under the final tune of GABA(A)R α(5) subunit activation in DGGCs at different ages.